Damoctocog Alfa Pegol for Hemophilia A Prophylaxis: An Italian Multicenter Survey - Ezio Zanon (MDPI AG, 2023)
Hemophilia A is characterized by a deficiency of clotting factor VIII (FVIII) requiring lifelong prophylactic treatment, typically with recombinant FVIII. In recent years, drugs with extended half-lives have become available, including damoctocog alfa pegol (Bayer S.p.A.). The clinical efficacy and safety of damoctocog alfa pegol were demonstrated in the PROTECT VIII phase II/III development program. To assess the physicians' experience and to collect data on prophylactic treatment with damoctocog alfa pegol, a monitoring survey was carried out among 15 Italian hemophilia centers. A total of 149 patients on treatment with damoctocog alfa pegol for at least 6 months were considered. Zero bleeds were reported in 75% of patients treated with damoctocog alfa pegol in the last 6 months; zero hemarthroses were reported in 82% of the same patients. Overall, 86% of patients with damoctocog alfa pegol reduced their monthly infusions. The estimated average reduction in IU/kg during prophylaxis with damoctocog alfa pegol, both monthly and annually, was around 17.5%. All involved clinicians were satisfied with damoctocog alfa pegol. Survey results suggest that damoctocog alfa pegol reduced the number of weekly infusions, annual bleeding, and joint bleeding rate in the majority of patients, improving joint health and patients' quality of life.